Modern Approaches To Diagnosis And Prevention Of Perinatal Outcomes In Pregnant Women With Pre-Term Birth - Karimova M.X.; Kayumova D.T (Universitas Muhammadiyah Sidoarjo, 2022)
Preterm birth (PR) is the main problem of perinatology in the world. Premature births are not only a medical but also a social problem, which is primarily due to their consequences for children - perinatal morbidity and mortality in premature newborns is 35-40 times higher than in full-term ones. A number of pregnancy complications are associated with vitamin D deficiency: termination of pregnancy in the I and II trimesters, the development of placental insufficiency, preeclampsia, disorders of the contractile activity of the uterus, and an increased risk of caesarean section. Vitamin D is a fat-soluble vitamin. Receptors for it are found in many tissues, such as the intestines, muscles, cells of the pancreas, prostate and ovaries, which explains the variety of clinical manifestations of vitamin D deficiency. According to a number of studies, it has been found that vitamin D promotes chorion vascularization, controls the secretion of various placental hormones , participate in the formation of the teeth and bones of the baby. Vitamin D deficiency leads to impaired calcium-phosphorus metabolism during pregnancy and increases the risk of fractures. Deficiency also affects the adaptation of the newborn, its development. In children with a lack of vitamin D in the body, rickets develops as a result of a violation of the mineralization of bone tissue. It is one of the most common diseases in infants and young children, and it also occurs in many children under the age of one.